Identification and Characterization of a Novel Epitope of ASFV-Encoded dUTPase by Monoclonal Antibodies - Shuai Zhang (MDPI AG, 2021)
Deoxyuridine 5′-triphosphate nucleotidohydrolase (dUTPase) of African swine fever virus (ASFV) is an essential enzyme required for efficient virus replication. Previous crystallography data have indicated that dUTPase (E165R) may serve as a therapeutic target for inhibiting ASFV replication; however, the specificity of the targeting site(s) in ASFV dUTPase remains unclear. In this study, 19 mouse monoclonal antibodies (mAbs) were produced, in which four mAbs showed inhibitory reactivity against E165R recombinant protein. Epitope mapping studies indicated that E165R has three major antigenic regions: 100–120 aa, 120–140 aa, and 140–165 aa. Three mAbs inhibited the dUTPase activity of E165R by binding to the highly conserved 149–RGEGRFGSTG–158 amino acid sequence. Interestingly, 8F6 mAb specifically recognized ASFV dUTPase but not Sus scrofa dUTPase, which may be due to structural differences in the amino acids of F151, R153, and F154 in the motif V region. In summary, we developed anti-E165R-specific mAbs, and identified an important antibody-binding antigenic epitope in the motif V of ASFV dUTPase. Our study provides a comprehensive analysis of mAbs that target the antigenic epitope of ASFV dUTPase, which may contribute to the development of novel antibody-based ASFV therapeutics.